Analisis Penggunaan Cloud Computing Pada Usaha Ramah Lingkungan Di Universitas Pertamina - Fajar Faizin; Muhammad Alviazra; Muh. Nur Yasin; Meredita Susanty (JURNAL TEKNOLOGIA, 2021)
Nowadays, with issues related to global occurrences, every industry or organization is required to protect the environment in order to remain sustainable. In recent years cloud computing has become a topic of discussion especially in this endeavor. Cloud computing has the potential to reduce power consumption, energy costs and gain costs. This has led to an increasing number of organizations in the private and public sectors that have led to cloud-based solutions or are seriously considering moving to cloud computing. However, the decision to use cloud computing will always require a complete analysis of the new options being offered in order to minimize risks. This paper will explain an analysis of the benefits, advantages and disadvantages of using cloud computing in environmentally friendly enterprises at Pertamina University.